A History of Health & Fitness: Implications for Policy Today - Shephard, Roy J. (Springer International Publishing, 2018)
This book provides a unique and succinct account of the history of health and fitness, responding to the growing recognition of physicians, policy makers and the general public that exercise is the most potent form of medicine available to humankind. Individual chapters present information extending from the earliest reaches of human history to the present day, arranged in the form of 30 thematic essays covering topics from the supposed idyll of the hunter-gatherer lifestyle and its posited health benefits to the evolution of health professionals and the possible contribution of the Olympic movement to health and fitness in our current society. Learning objectives are set for each topic, and although technical language is avoided as far as possible, a thorough glossary explains any specialized terms that are introduced in each chapter. The critical thinking of the reader is stimulated by a range of questions arising from the text context, and each chapter concludes with a brief discussion of some of the more important implications for public policies on health and fitness today and into the future. The material will be of particular interest to graduate and undergraduate students in public health, health promotion, health policy, kinesiology, physical education, but will be of interest also to many studying medicine, history and sociology.